2020
DOI: 10.1111/irel.12263
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Drivers of Extensive Work Effort: Are Long Hours Always Detrimental to Well‐being?

Abstract: Is extensive work effort always detrimental to professionals' well-being? We argue that the link between extensive work effort and well-being depends on the reasons why professionals work extended hours. Drawing on self-determination theory and data from an international consultancy firm, we show that extrinsically driven work effort is negatively related to well-being, while intrinsically driven work effort is positively related to well-being. A reinforcing effect seems to exist between the two types of motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…Pursuing career outcomes such as salary increases and job promotions are important motivations for employees to work over-time. Employees who are intrinsically motivated to work overtime are enthusiastic about increasing their work commitment and deriving satisfaction from the increased work commitment and job outcomes [28]. Employees with high self-fulfilment requirements are more likely to work overtime voluntarily [29].…”
Section: The Overtime Culture In the Internet Industrymentioning
confidence: 99%
“…Pursuing career outcomes such as salary increases and job promotions are important motivations for employees to work over-time. Employees who are intrinsically motivated to work overtime are enthusiastic about increasing their work commitment and deriving satisfaction from the increased work commitment and job outcomes [28]. Employees with high self-fulfilment requirements are more likely to work overtime voluntarily [29].…”
Section: The Overtime Culture In the Internet Industrymentioning
confidence: 99%
“…Here, because motivations have long been viewed as an important individual characteristic predicting psychological functioning and well‐being (Vallerand, 1997), we focus on individual motivations for engaging in intensive work. Such motivations can credibly exist separate from job discretion (Avgoustaki & Cañibano, 2020), so a focus on individual motivations plausibly offers a productive way forward to improve our understanding of the differences in work‐related well‐being among employees performing intensive work.…”
Section: Work‐intensity Motives and Employee Well‐beingmentioning
confidence: 99%
“…All the above studies focused on the extrinsic and intrinsic motivations for an employee's job as a whole. Nevertheless, one recent study examined the well‐being implications of extrinsically and intrinsically motivated overtime, an effort dimension distinct from work intensity, in a sample of employees at an international consultancy firm (Avgoustaki & Cañibano, 2020). In their sample of professionals, the authors showed that extrinsically driven overtime was negatively related, while intrinsically driven overtime was positively related, to employee well‐being, although the number of overtime hours per se was negatively related to well‐being.…”
Section: Work‐intensity Motives and Employee Well‐beingmentioning
confidence: 99%
See 2 more Smart Citations